Microwave-Hydrothermal Tuning of Spinel-Type Co3O4 Water Oxidation Catalysts - Lienau, Karla; Triana, C. A.; Reith, Lukas; Siol, Sebastian; Patzke, Greta R. (Frontiers in Chemistry, 2020)
Water oxidation is the bottleneck reaction for overall water splitting as a direct and promising strategy towards clean fuels. However, the development of robust and affordable heterogeneous water oxidation catalysts remains challenging, especially with respect to the wide parameter space of synthesis and resulting material properties. Oxide catalysts performance in particular has been shown to depend on both synthetic routes and applied catalytic test methods. We here focus on spinel-type Co3O4 as a representative case for an in-depth study of the influence of rather subtle synthetic parameter variations on the catalytic performance. To this end, a series of Co3O4 samples was prepared via time-saving and tunable microwave-hydrothermal synthesis, while systematically varying a single parameter at a time. The resulting spinel-type catalysts were characterized with respect to key materials properties, including crystallinity, oxidation state and surface area using a wide range of analytical methods, such as PXRD, Raman/IR, XAS and XPS spectroscopy. Their water oxidation activity in electrocatalytic and chemical oxidation setups was then compared and correlated with the obtained catalyst properties. Both water oxidation methods displayed related trends concerning favorable synthetic parameters, namely higher activity for lower synthesis temperatures, lower precursor concentrations, addition of hydrogen peroxide and shorter ramping and reaction times, respectively. In addition to the surface area, structural features such as disorder were found to be influential for the water oxidation activity. The results prove that synthetic parameter screening is essential for optimal catalytic performance, given the complexity of the underlying performance-properties relationships.